MANKAMENTY SYSTEMU WYBORCZEGO DO SEJMU RP NA TLE OSTATNICH DOŚWIADCZEŃ WYBORCZYCH - Strzałkowski, Tomasz (Wydział Prawa i Administracji UAM, 2008)
The first part of the paper identifies the shortcomings o f the electoral law currently binding in Poland in respect of parliamentary (Seym) election. The observations have been based on the experience of the elections carried out in Poland in 2005 and 2007. It is suggested that the manner in which eligible voters are registered and how the vote is carried out outside Poland requires some modifications. Alternative forms o f voting should also be considered. As the recent election has shown, which has also been subsequently reflected in promises made by politicians to amend the respective law, new solutions to improve the system must be developed. Also the status o f international observers should be precisely clarified. In the author’s opinion changes are also needed in the regulations governing the election campaign, and, in particular, access to public media and electoral silence. The other part of the paper focuses on the assessment of the existing electoral system, showing how it may influence the results o f the elections. The major defects or shortcomings of the system have been identified. The role of large political parties in the electoral process and the significance of the position of a candidate on the electoral roll have been shown. Further, the importance of a proper relationship between the elector and the deputy has been signalled.
PARLIAMENTARY ELECTION SYSTEM IN POLAND AND ITS SHORTCOMINGS ON THE EXAMPLE OF THE RECENT ELECTION TO THE SEYM